Aspek Hukum Pertambangan Ilegal dan Dampaknya terhadap Kelestarian Fungsi Lingkungan Hidup Studi Desa Roko Kecamatan Galela Barat (International Forum of Researchers and Lecturers, 2024)
Illegal mining is rife in the Halmahera area, North Maluku Province, one of which is in Roko village, West Galela District. Mining without a permit, known as PATI, certainly has a big impact, not only on state income and the preservation of environmental functions, but also triggers social conflict among residents, both between illegal miners and local residents and between fellow miners who want to control certain areas. It doesn't stop there, since the presence of PT. Halmahera Jaya Maining with its modern technology is expected to be managed in accordance with legal and regulatory standards, but the environmental situation is getting worse because it is not equipped with an AMDAL. In this research the author used Empirical Juridical Research by comparing two Legal Research methods, the juridical approach was studied based on Law Number 4 of 2009 as amended by Law Number 3 of 2021 concerning Minerals and Coal in conjunction with Law Number 32 of 2009 concerning Management and Environmental Conservation, as last amended by Law Number 11 of 2020 concerning Job Creation, is carried out empirically. Data collection through monitoring and interviews with residents of Roko Village on behalf of Etus Pali. In studies and field studies, it was found that residents were worried about the presence of PT HJM and illegal mining carried out by residents without permission, which had an impact on the environment. Therefore, it is necessary to carry out integrated supervision and law enforcement by related parties against companies that ignore legal provisions and socialization and advocacy needs to be provided to illegal miners.